Perlindungan Hukum Pemegang Saham Terhadap Tindakan Penarikan Kembali Saham Ditinjau Dari Undang-Undang Perseroan Terbatas - Dimas Pasha Hafidz; Mohammad Rafi Al Farizy (Jurnal Ilmu Kenotariatan, 2023)
One of the corporate actions that the Company can take is to reduce capital. Reducing the capital carried out by the Company can be done in 2 ways, namely recalling shares or reducing the nominal value of shares based on Article 47 paragraph (1) of Law Number 40 of 2007. The corporate action to reduce capital must still protect the interests of shareholders. However, the provisions of Law Number 40 of 2007 are still unable to protect the interests of shareholders in terms of corporate actions to reduce capital because there is still legal ambiguity in the phrase "reasonable price" in Article 61 of Law Number 40 of 2007 and the absence of norms regarding the mechanism reduction of capital through shares with a classification that can be withdrawn. This research is a normative research that uses a statutory approach and an analytical approach. The results of this study are that there are still weaknesses in the Limited Liability Company Law, where there is no regulation regarding a fair price in a share recall transaction through a share withdrawal mechanism with a retractable classification and no explanation regarding the definition of "reasonable price" in the share recall mechanism. through shares that have been bought back by the Company. KEYWORDS: Capital Reduction, Fair Price, Shareholders.